Teachers’ Spiritual Competence as The Foundation for Holistic Guidance of Children with Special Needs in Inclusive Madrasah Ibtidaiyyah - Umi Ivayatuz Zulva Nurmala; Putri Aulia; Rafiqotul Husna; Izzati Ramadhani Herry (Universitas Wahid Hasyim Semarang, 2025)
This study aims to analyze the role of teachers' spiritual competence as the foundation for implementing inclusive education in Islamic elementary schools (Madrasah Ibtidaiyah) through a qualitative library research approach. Data were collected from 48 scholarly works, reduced to 12 core sources, and analyzed using content and conceptual analysis. The findings reveal that teachers' spirituality serves as a moral, reflective, and emotional force guiding inclusive practices. Drawing on Spiritual Intelligence Theory and Inclusive Pedagogy, the study shows that spiritually intelligent teachers demonstrate empathy, patience, and moral commitment toward student diversity. The integration of these theories formulates an Islamic Inclusive Pedagogy paradigm that combines tauhidic, compassionate (rahmah), and just (adl) values in teaching. It concludes that Islamic spirituality–based inclusion fosters a holistic education model that nurtures empathy, justice, and human dignity.